PENGARUH UNSUR KE-EMPAT TERHADAP TRANSFORMASI FASA DAN EFEK INGAT BENTUK (SHAPE MEMORY EFECT) PADUAN Ti- Ni-Cu[The Influence of Fourth Element on Phase Transformation and Shape Memory Effect (SME) of Ti-Ni-Cu Alloys] - Mabruri, Efendi; Sriyono, Bambang; Adjiantoro, Bintang; Adnyana, D N (Jurnal Metalurgi, 2013)
Among the existing shape memory alloys, Ti-Ni-Cu is the most atractive alloy for actuator application because it shows quick actuation response due to its narrow transformation temperature hysteresis. This paper reports the effect of the fourth element Fe, Sn, Cr, Nb, Co, Mo on the phase transformation of Ti-Ni-Cu alloys. In addition, the shape memory effect (SME) of the Ti-Ni-Cu and Ti-Ni-Cu-Fe alloys in both cold worked and annealed conditions is discussed. The experimental results showed that the fourth element added into the Ti-Ni-Cu alloys modified the phases presented in the alloys by different ways, i.e. by deppressing both B19’(NiTi) and B19’(TiNi0.8Cu0.2) phases for Fe, Co, Nb; by revealing precipitate phases for Sn and Cr; and by deppressing B19’ (TiNi0.8Cu0.2) phase for Mo. With respect to the alloys condition, it was showed that the SME exhibited by the annealed alloys was larger than that exhibited by the cold worked alloy. Furthermore, it was found that the SME of Ti-Ni-Cu-Fe alloy was lower than that of Ti-NiCu alloy. Microstructure observation showed that the martensite phase of Ti-Ni-Cu-Fe alloy was characterized by lower volume fraction and larger lath size compared to those of the Ti-Ni-Cu alloy.